C103. Pathogenesis, Biomarkers, and Risk Factors for Interstitial Lung Disease: From Bench to Bedside 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a5174
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory Microbiome In Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease of unknown cause. Current evidence suggests that it arises in genetically susceptible individuals as a consequence of an aberrant wound-healing response following repetitive alveolar injury. Overt respiratory infection and immunosuppression carry a high mortality, while polymorphisms in genes related to epithelial integrity and host defence predispose to IPF. Recent advances in sequencing technologies have allowed the use of molecular micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We used sequence-based culture-independent methodologies to quantify both the numbers of bacterial genomes and the community composition of specimens collected by bronchoalveolar lavage. Some of the results of these studies have been previously reported in the form of an abstract (18).…”
Section: Methodsmentioning
confidence: 96%
“…We used sequence-based culture-independent methodologies to quantify both the numbers of bacterial genomes and the community composition of specimens collected by bronchoalveolar lavage. Some of the results of these studies have been previously reported in the form of an abstract (18).…”
Section: Methodsmentioning
confidence: 96%
“…To date, there has been no assessment of the role of the respiratory microbiome in the pathogenesis, progression or exacerbation of IPF. However, it is anticipated that the assessment of the lung microbiome in IPF will shed important light on the role played by bacterial colonisation of the lower airways in the development and progression of fibrosis [47].…”
Section: The Role Of Bacteria In the Pathogenesis Of Ipfmentioning
confidence: 99%
“…[ Molyneaux et al (2012). We then focus on analyzing genera from both phyla Bacteroidetes and Firmicutes given their important status in normal lungs (Cui et al, 2014).…”
Section: Simulation Resultsmentioning
confidence: 99%